The impact of time-restricted eating on circulating factors, insulin sensitivity and circadian rhythms - Kennedy, Devin, author; Broussard, Josiane, advisor; Braun, Barry, committee member; Stephens, Jaclyn, committee member (Colorado State University. Libraries, 2020)
Purpose: Obesity has been steadily increasing over several decades. In 2008, prevalence rates of obesity were reported at over 300 million people, defined as a body mass index of >30kg/m2. For years, scientists have tried to find "solutions" to obesity. While obesity prevention measures taken in childhood might result in decreased adulthood obesity, childhood prevention measures are not common, and obesity is often a health issue in adulthood. Negative energy balance and caloric restriction is most effective for reducing body weight, and studies have reported beneficial effects such as reduced fasting glucose and insulin, reductions in body weight [1], significantly higher insulin sensitivity, significantly lower BMI [2], reduced β-cell sensitivity [3], and reduced fasting glycemia and fasting insulinemia [4]; however, long-term adherence to caloric restriction is low. Certain fasting practices are emerging as promising possible solutions to help combat obesity. Fasting practices have resulted in improvements in cardiometabolic health including but not limited to protection from obesity [5], improved LDL and HDL cholesterol, reduced HbA1c and c-reactive proteins, [6], cell proliferation, and body weight [7]. Intermittent fasting is one method by which an individual can reduce body weight but also improve numerous cardiometabolic factors. However, research exploring intermittent fasting (IF), specifically time-restricted eating (TRE), as a method of improving cardiometabolic health is limited. Circadian rhythms might be the reason that aligning feeding windows to earlier in the day is showing these benefits. Currently, a gap in the knowledge exists as to whether circadian rhythms play a role in contributing to the metabolic benefits that are conferred by TRE, or if the timing of the food intake/duration is what results in the benefits. Therefore, our objective was to examine the effects of TRE on 24-hour glucose homeostasis and nighttime patterns of circulating factors (glucose, insulin, free fatty acids, triglycerides, and glycerol) as well as insulin sensitivity and the central circadian clock. Methods and results: This study employed a consecutive design. Eight healthy adults (6F; 27±4 y; 22.6±2.1 kg/m2; mean ± SD) completed a 2-week protocol. During Week 1 participants were instructed to consume their daily calories over a 13h period (control condition). In Week 2, participants were instructed to consume their daily calories over an 8h period (TRE condition). Specified mealtimes were pre-determined based on the habitual sleep and wake time for each individual participant. At the end of each week, participants were admitted to the Sleep and Metabolism Laboratory for an overnight stay that involved hourly blood samples. Plasma samples were analyzed for glucose, insulin, free fatty acids (FFA), lactate, triglycerides, and glycerol. The plasma analyses indicated that TRE decreased glucose variability during sleep (p=0.03), reduced nighttime insulin concentrations (p=0.005), increased nighttime FFA levels (p=0.04), increased nighttime triglycerides (p=0.006) and increased nighttime glycerol (p=0.02). TRE did not impact glucose variability during wakefulness (p = 0.49), nighttime glucose (p = 0.39), insulin sensitivity (MATSUDA-ISI, p = 0.38), or central circadian rhythms. Conclusion: The observed changes in nighttime glucose variability and insulin levels could represent mechanisms by which TRE can improve metabolic homeostasis in healthy lean individuals. Future studies are warranted to determine whether TRE can improve metabolic homeostasis in people at risk for diabetes such as people with overweight and obesity, and impaired glucose tolerance.
Keywords: insulin sensitivity; nighttime factors; time-restricted eating; intermittent fasting; circadian rhythms; nocturnal factors